Antimicrobial Activity And Characterization of Some Oxazole, Thiazol And Quinoline - Amjad Gali. Eliwi1, Safaa. Abdul-Hameed. Dadoosh1, Zainab Z. Mohammed Ali 1, Abdul Jabar Kalaf Atia1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
New Heterocyclic compounds derivatives comprising 1,3-oxazole, chalcone ,thiazole, pyrimidine, quinolone moieties are reported. New derivatives of Quinazolin-4 (3H)-one ring comprising Schiff’s bases,(1,3,4-Thiadiazole),(1,3,4-Oxadiazole) and (1,2,4-Triazole), Thiaurease moieties are reported. Compounds (1), (2) and (5) were synthesized by reaction of benzoyl chloride with urea , thiourea and anthranilic acid respectively , then compounds (1)and (2) were converted into(3a-c) and (4a-c) derivatives. While compound (5) reaction with urea to convert to compound (6) which was converted to (7a-c) . chalcone derivatives (9a,b ) were readily obtained by reaction of compound (8) with different aldehydes, Compounds (9a , b) were converted into (10a,b) and (11a,b) The structure of these compounds has been established on the basis of their spectral data FTIR and 1HNMR. These compounds were tested for invitro antibacterial activity against Escherichia coli, Sepidermidis, S.aureusand Klebseillastandard methods. These synthesized compounds have been shown moderate to good antibacterial activity.